Moshe Hartal, Danny Sion, Eliezer Stern & Ayelet Tatcher, ̒Akko II The 1991–1998 Excavations. The Early Periods - Rosenthal-Heginbottom, Renate (Journal of Hellenistic Pottery and Material Culture, 2017)
To date, there is no comprehensive corpus of Hellenistic imported and local ceramics from the eminent maritime metropolis of ʻAkko–Ptolemais. Hence, the present publication of substantial ceramic ﬁnds presented and discussed by Andrea M. Berlin and Peter J. Stone will serve as an essential compilation and as an indispensable tool for future research, complementing the previous study by Dalit Regev. The ceramic ﬁnds originate from two locations, the Courthouse site and the Hospitaller Compound, where excavations were carried out on behalf of the Israel Antiquities Authority between 1991 and 1998.